DYNAMIC RESPONSE ANALYSIS BOX GIRDER BRIDGE UNDER HIGH SPEED RAILWAY LOAD - Zirads, Bob
High speed railway mostly dominated by elevated structure because its vertical alignment adjustment are limited and sensitive. The various topography condition and land occupation in the several city are very limited makes it impossible to always use the subgrade railway. High speed train is similar with the conventional train observed by their axle configuration under certain distance that could cause a repetitive load behavior (external load frequency) that could trigger resonance to the bridge structure. The resonance issue for structure needs to be cleared since it could lead to safety and convenience issue for the railway passenger. For example, the vertical deck acceleration for railway bridge in Eurocode (EN 1990:2002 A2) and China Code (TB 10002.3-2005) is limited to 3.5 m/s2 . For railway with ballast, structural response need to be confined to reduce the risk of the loss of ballast interlocking that could lead to structural failure. Thus, the objective of this thesis is to comprehend and ascertain dynamic response of both type of box girder that has characteristic difference of structural and operated train. The analysis done with 3 phase, first phase is to observe the single axle load, second phase is to use the multi axle with conventional trainset load and the third phase is to use the multi axle of high speed railway load. Response on comparison of both analysis static and dynamic, structural response of the slow speed train shows not much different to structural response against static movement. The high speed train load gave varied response and much bigger than the structural response against static movement. The usage if dynamic magnification factor (DMF) required by the code are considered conservative and could represent the analysis response result of dynamic response analysis as long as the schemed load and the observed structure is not categorized as irregular structure, this explain the reason why the code limited the length of the bridge and schemed train operational velocity thereout the certain range or not categorized as simple structure needs dynamic analysis.